Examining Criminal Justice Practitioners’ Views on Collateral Consequences Policy - Goulette, Natalie (American journal of criminal justice, 2018)
With the recent emphasis on reentry and the reintegration of offenders back into society, both academics and policy makers have voiced concern over both the process of applying collateral consequences in a particular case and the expanding number of collateral restrictions, some of which are quite severe. Many of these restrictions create significant barriers to reintegration for offenders released from incarceration. While reforms have been proposed, there is a lack of research examining the perceptions of criminal justice actors about collateral consequences of conviction. As parties most familiar with the application of consequences in cases, and the burdens they place on involved parties, the present study surveyed practitioners in a large Midwestern state. The findings suggest that judges, defense attorneys, probation and parole supervisors, and prosecutors are troubled by the role of collateral consequences in offender reentry and are not opposed to repealing or reforming some of these policies. Further, there are significant differences between practitioner groups as to reforms that should be implemented within the state’s criminal justice system.